Biomass and composition of protistan grazers and heterotrophic bacteria in the Costa Rica Dome during summer 2010 - Freibott, Alexandra (J Plankton Res, 2016)
We investigated biomass and composition of heterotrophic microbes in the Costa Rica Dome during June–July 2010 as part of a broader study of plankton trophic dynamics. Because picophytoplankton (<2 μm) are known to dominate in this unique upwelling region, we hypothesized tight biomass relationships between size-determined predator–prey pairs (i.e. picoplankton–nano-grazers, nanoplankton–micro-grazers) within the microbial community. Integrated biomass of heterotrophic bacteria ranged from 180 to 487 mg C m(−2) and was significantly correlated with total autotrophic carbon. Heterotrophic protist (H-protist) biomass ranged more narrowly from 488 to 545 mg C m(−2), and was comprised of 60% dinoflagellates, 30% other flagellates and 11% ciliates. Nano-sized (<20 μm) protists accounted for the majority (57%) of grazer biomass and were positively correlated with picoplankton, partially supporting our hypothesis, but nanoplankton and micro-grazers (>20 μm) were not significantly correlated. The relative constancy of H-protist biomass among locations despite clear changes in integrated autotrophic biomass, Chl a, and primary production suggests that mesozooplankton may exert a tight top-down control on micro-grazers. Biomass-specific consumption rates of phytoplankton by protistan grazers suggest an instantaneous growth rate of 0.52 day(−1) for H-protists, similar to the growth rate of phytoplankton and consistent with a trophically balanced ecosystem dominated by pico-nanoplankton interactions.